Importance of fluorescence lifetimes for efficient indoline dyes in dye-sensitized solar cells1. Issue 71 (2nd August 2015) - Matsui, M.; Aoki, R.; Nishiwaki, D.; Kubota, Y.; Funabiki, K.; Jin, J.; Yoshida, T.; Higashijima, S.; Miura, H.
<x xml:space="preserve">Abstract</x> To make a molecular design of efficient indoline dyes, fluorescence lifetimes should be longer than ca. 0.8 ns in chloroform, in addition to suitable HOMO and LUMO levels and bathochromic UV-vis absorption bands.